Perspectives for progress - Female athlete triad and relative energy deficiency in sport - Williams, N. I.; Koltun, K. J.; Strock, N. C. A.; de Souza, M. J. (Exercise and Sport Sciences Reviews, 2019)
We examine the scientific evidence supporting The Female Athlete Triad and Relative Energy Deficiency in Sport (RED-S) syndromes. More research is necessary to advance the understanding of both syndromes; however, it is premature to consider RED-S as an evidence-based syndrome. Future research should specifically define RED-S components, determine its clinical relevance, and establish the causality of relative energy deficiency on RED-S outcomes.